(untitled) - Ehrenberg, Ronald G. (Reading, MA., 2000)
A textbook designed for a one-semester or one-quarter course at the undergraduate or graduate level for students who may not have extensive backgrounds in economics. It develops the modern theory of labor market behavior, summarizes empirical evidence that supports or contradicts each hypothesis, and illustrates in detail the usefulness of the theory for public policy analysis. This revised and updated edition also adds a new chapter on earnings inequality.
Keywords: Labor economics,Labor policy,Personnel management,Comparative industrial relations